Rendering Artful and Empathic Arts-Based Performance as Action (LEARNing Landscapes, 2022)
There is a critical need to consider ways to enrich the educational experiences and well-being of adolescents when the lack of empathy in the world is high. This paper presents the concepts of Artful Empathy and Artful and Empathic Learning Ecology. The concepts are exemplified from a multi-site case study within Australian secondary visual art studio classrooms. The article demonstrates how learning and making art in an artfully empathic ecology can support the legitimacy of diverse and marginalized voices. Arts-based performative approaches may facilitate empathic knowing across disciplines with global traction.
Keywords: empathic education; well-being; artmaking; artful empathy